Indigenous Posthumans: Cyberpunk Surgeries and Biotech Boarding Schools in File Under Miscellaneous and SyFy's Helix. Issue 1 (2016) - Attebery, Stina
Abstract : Jeff Barnaby's (Mi'gMaq) film File Under Miscellaneous and the SyFy series Helix connect Indigenous apocalypse to forms of biomedical posthumanism, bringing together Achille Mbembe's necropolitics of the colony with Gerald Vizenor's concept of survivance. Both Vizenor and Mbembe imagine ways that colonized subjects could fight back when they are "kept alive but in a state of injury "—a description originally referring to slavery, but which I use for Indigenous experimental subjects. By replacing survival with human enhancement, these texts transform Mbembe's interrelated categories of martyrdom and survival into zombie posthumanism and transhumanism, developing Indigenous posthumanism as a third option through this dialectic.